EL ÍNDICE DE POTENCIALIDAD DE LAS INDUSTRIAS CULTURALES Y CREATIVAS - Dr. Antonio CASTRO-HIGUERAS,Dr. Miguel DE AGUILERA MOYANO, (Fonseca, Journal of Communication, 2023)
The cultural and creative industries are regarded as a strategic sector in today’s knowledge economy and are therefore encouraged by government policies. The link between culture, creativity and economic development has flourished in Spain in recent years, to the extent that by 2014 the sector accounted for 3.5% of the country’s GDP and 3% of all jobs. Such an important sector requires a diagnostic tool to support decision making